Protection of organic cereals from insect and rodent pests in a warehouse by combined use of traps and sticky tapes - Kljajić, Petar; Andrić, Goran; Jokić, Goran; Pražić Golić, Marijana; Blažić, Tanja; Jovičić, Ivana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
Several options of protection of organic cereals (winter and spring wheat, rye and maize) from insect and rodent pests, using a combination of traps (with or without pheromone/attractant) and sticky tapes and no chemicals, were tested in a warehouse over the summerspring season of 2019/2020. Temperature in the warehouse was 14-29°C and humidity around 50%. The average grain moisture of winter and spring wheat and rye was 10-11%, while it was 12-14% in maize grain, and the average grain temperature of all cereals was 13-27°C. Regarding stored-product insect pests, five coleopteran, two moth and one Psocoptera species weredetected, and the coleopterans predominated (98.5%) along with secondary pest insects (94.0%). Regarding rodents, only specimens of Mus musculus were found throughout the test period, their maximum monthly frequency being 72 (in January 2020). A combination of traps (with or without pheromones) and sticky tape barriers was found to provide an effective tool for trapping insects. Also, snap traps and trapping boxes for killing rodents, when used simultaneously with sticky tape barriers, were found to provide good protectionof cereals from house mice. The pest control effect was also confirmed by collecting samples of organic cereal grain, which showed no significant presence of stored-product insects or grain damage (0.94% and 0.96% in spring wheat and rye, respectively) at the end of the test period. The results showed a great potential of combined application of traps and sticky tapes for protecting organic cereals in horizontal bulk storages, but the use of chemicals approved for organic food production would be required under extended storage periods.
Keywords: cereals; insects; rodents; traps; sticky tapes; warehouse